Maternal and perinatal outcomes in pregnancies conceived after infertility treatment at a tertiary care centre in Chhattisgarh: a prospective observational study - Bhad, Sonalika A.; Kamra, Sangeeta; Kaur, Prabhdeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Infertility affects 10-15% of couples in India, with increasing reliance on ovulation induction, intrauterine insemination (IUI), and assisted reproductive technologies (ART). Pregnancies conceived following infertility treatment have been associated with higher maternal and perinatal risks. Objective of this study was to evaluate maternal and fetal complications in pregnancies conceived after infertility treatment and identify factors influencing maternal-neonatal morbidity. Methods: A prospective observational study was conducted over 12 months at a tertiary care center in Chhattisgarh. Sixty antenatal women who conceived after infertility treatment (OI, IUI, IVF, fertility-enhancing surgery) were enrolled. Demographic, clinical, obstetric, and neonatal outcomes were analysed using descriptive statistics. Results: Mean maternal age was 31.8 years; 68.3% had primary infertility. PCOS was the most common female cause (56.7%). IVF accounted for 40% of conceptions, while OI+TI accounted for 43.3%. Medical complications included gestational hypertension (26.7%), GDM (26.7%), IHCP (16.7%), and preeclampsia (3.3%). PROM occurred in 15%, and preterm labor in 5%. LSCS rate was high (78.3%), with 87.5% of IVF pregnancies delivered by LSCS. Neonatal outcomes showed 31.8% low birth weight and 7.6% very low birth weight infants. Preterm delivery occurred in 23.3%. Conclusions: Pregnancies conceived after infertility treatment especially those resulting from IVF, older maternal age, PCOS, obesity, and long-standing infertility were associated with higher risks of hypertensive disorders, GDM, PROM, preterm birth, LSCS, and low birth weight. Enhanced antenatal surveillance and multidisciplinary management are essential to optimize outcomes.